Development and validation of computational fluid dynamics models for the coupled simulation of heat transfer and fluid flow in the coral microenvironments - Ong, Robert Harsono (Curtin University, 2014)
This thesis explored the temperature deviations between coral surface temperature and ambient seawater temperature that likely determines the microscale processes involved in coral bleaching. The work presented here applied Computational Fluid Dynamics (CFD) technique coupled with hydrodynamic modelling and ray-tracing to predict coral surface warming due to the effects of stressors. This thesis demonstrates that modelling microscale temperature could yield important insights into thermoregulation in corals, which may lead to a more effective reef management.